1986
DOI: 10.1016/0014-5793(86)80561-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbachol and oxytocin stimulate the generation of inositol phosphates in the guinea pig myometrium

Abstract: In the guinea pig myomet~um prelabelled with ~~5[2-3H]inositol, carbachol and oxytocin enhanced a concentration-dependent and rapid release of IP, which preceded that of IP, and IP,. The specific receptormediated phospholipa~ C activation degrading PIP, to IP, did not require the presence of extra~llular Caz+. The ionophore A23187 as well as K+ depolarization failed to increase inositol phosphate accumulation. It is proposed that IP, could have a role in the contraction of uterine smooth muscle elicited by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 15 publications
1
84
0
Order By: Relevance
“…Moreover, m4 receptors have also been shown to mediate Stimulation of phosphoinositide hydrolysis (Peralta et al 1988;Ashkenazi et al 1989). Both second messenger responses have been reported to occur upon muscarinic Stimulation of the immature guinea-pig uterus (Leiber et al 1984;Mare et al 1986). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, m4 receptors have also been shown to mediate Stimulation of phosphoinositide hydrolysis (Peralta et al 1988;Ashkenazi et al 1989). Both second messenger responses have been reported to occur upon muscarinic Stimulation of the immature guinea-pig uterus (Leiber et al 1984;Mare et al 1986). …”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have found that agonist-sensitive PIP2 breakdown is inhibited by pertussis toxin [14,15] and pertussis toxin is believed to exert its effects on metabolism via the inactivation of G proteins. Other studies have found that agonist-sensitive PIP2 breakdown is insensitive to pertussis toxin in several tissues [12,13]. Since PIP2 breakdown in nearly all of the latter tissues is stimulated by either GTP, GTPyS, or by AlF4 -it appears likely that a pertussis toxininsensitive G protein is required to mediate the effects fo agonists on phospholipase C in such tissues.…”
Section: Discussionmentioning
confidence: 93%
“…These experiments indicate that one or more G proteins most likely mediate the action of a contractile agonist on phospholipase C directly. Further evidence in support of this theory comes from the work of those who have shown that the ion AlF4 -can stimulate the breakdown of PIP2 to form IF'3 in Cells from ileum [2O] and myometrium [12], as well as from other tissues [lo]. Some of these studies have found that agonist-sensitive PIP2 breakdown is inhibited by pertussis toxin [14,15] and pertussis toxin is believed to exert its effects on metabolism via the inactivation of G proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenohypophysis VIb receptors also stimulate phospholipase C. Oxytocin receptors activate phospholipase C and induce an increase in the cytosolic Ca 2+ concentration, which results in strong contractions of the uterus at term (Mirronneau, 1976;Antoni, 1986;Marc et al, 1986). Single amino acids have been found to be important for the activation of this family of receptors.…”
Section: Receptors -Gene and Proteinmentioning
confidence: 99%